Réponses

2013-02-26T15:12:12+01:00

1. domf = R

2. F'(x) = [(-4x+1)(x²+x+1)-(2x+1)(-2x²+x+1)]/(x²+x+1)² =(-3x² -6x)/(x²+x+1)²

3.

 

x       -oo                   -2                        0               oo

f'(x)            -               0             +         0       -

f(x)    -2     \               3             /          1      \          -2

 

f'(2) = -24/49

f(2) = -0,714 

T : y + 0,714 = -24/49(x-2)

 

exercice 2

pi/8 et 7pi/8 comme 3pi/8 et 5pi/8 sont supplémentaires ils ont des cos opposés et des sinus égaux

donc (cos pi/8 + cos7pi/8) + (cos3pi/8 + cos 5pi/8) = 0 + 0 = 0

et (sin pi/8 - sin7pi/8) + sin5pi/8 - sin3pi/8 ) = 0 + 0 = 0